KEPEMIMPINAN PENDIDIKAN TRANSFORMASIONAL DAN PARTISIPATIF: MEMBANGUN BUDAYA INKLUSIF DAN INOVATIF - Imaduddin, Muhammad Faris; Afdal, Muhammad; Victorynie, Irnie (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study aims to examine the practices of transformational, participatory, and digital leadership within the context of primary schools in the digital era, using a case study at SD Islam Al Ilmu Bekasi. Employing a qualitative phenomenological approach, data were collected through in-depth interviews with the school principal and the vice principal of curriculum affairs. The findings reveal that the integration of these three leadership approaches fosters an inclusive, collaborative, and technologically adaptive school culture. Transformational leadership is manifested through individual empowerment and the inspiration of a shared vision, while participatory leadership facilitates collective decision-making and teacher innovation. Meanwhile, digital leadership enhances management efficiency through the optimization of technologies such as DAPODIK and online platforms. This study contributes conceptually to 21st-century educational leadership models and underscores the importance of collaboration, humanistic values, and technological adaptation in the sustainable management of educational institutions.